2018
DOI: 10.3847/1538-3881/aae1f2
|View full text |Cite
|
Sign up to set email alerts
|

Exoplanet Modulation of Stellar Coronal Radio Emission

Abstract: The search for exoplanets in the radio bands has been focused on detecting radio emissions produced by the interaction between magnetized planets and the stellar wind (auroral emission). Here we introduce a new tool, which is part of our MHD stellar corona model, to predict the ambient coronal radio emission and its modulations induced by a close planet. For simplicity, the present work assumes that the exoplanet is stationary in the frame rotating with the stellar rotation. We explore the radio flux modulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…Many optional parameters governing how image alignment, PSF fitting and sky subtraction are performed may be altered within Dolphot, and in cases of severe stellar crowding, modifying these parameters can result in deeper, more complete photometric catalogs (e.g. Williams et al 2014;Cohen et al 2018a). Therefore, we adopt the parameters used by Williams et al (2014) given the crowded nature of our fields (e.g.…”
Section: Preprocessing and Photometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Many optional parameters governing how image alignment, PSF fitting and sky subtraction are performed may be altered within Dolphot, and in cases of severe stellar crowding, modifying these parameters can result in deeper, more complete photometric catalogs (e.g. Williams et al 2014;Cohen et al 2018a). Therefore, we adopt the parameters used by Williams et al (2014) given the crowded nature of our fields (e.g.…”
Section: Preprocessing and Photometrymentioning
confidence: 99%
“…Our per-filter photometric quality cuts are based on two primary criteria: The first is examination of the recovered values for input artificial stars over a range of position (i.e., projected stellar density), color and magnitude (see below), under the hypothesis that the loci in (recovered) parameter space which are devoid of artificial stars should be occupied only by non-stellar or spurious sources in the raw observed catalogs (e.g. Cohen et al 2018a). The second criterion is examination of observed sources passing and failing a proposed set of quality cuts in both position-color-magnitude space as well as visual inspection of accepted and rejected sources in the deep drizzled reference images to ensure that artifacts such as diffraction spikes are completely eliminated.…”
Section: Preprocessing and Photometrymentioning
confidence: 99%
“…The advent of high-resolution near-infrared (NIR) imagers equipped with Multi Conjugate Adaptive Optics (MCAO) facilities mounted at ground-based 8-10 m class telescopes opened a new line of investigation, arousing the interest of astronomers in the Galactic bulge and its bulge GC system (e.g. Saracino et al 2015Saracino et al , 2016, see also a complementary study based on deep NIR observations with the Hubble Space Telescope (HST) recently carried out by Cohen et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the authors found evidence of the presence of two red HBs separated by ≈ 0.1 mag in the K s band. In a very recent work performed using the IR channel of the HST/WFC3, Cohen et al (2018) imaged the MS of NGC 6569 also in the NIR, sampling a few magnitudes below the MS-TO and highlighting the presence of an extension of the HB blueward of the red clump.…”
Section: Introductionmentioning
confidence: 99%
“…There appears to be a concentration of GCs with a metallicity of [Fe/H]∼ −1.0 together with a blue horizontal branch (e.g., Bica et al 2016, Cohen et al 2018. Field halo stars with [Fe/H]∼ −1.0 are very rare because this is the high end of the halo metallicity distribution function (e.g., An et al 2013); the distribution of globular cluster metallicities from Harris (1996Harris ( , edition 2010 shows a small peak at [Fe/H]∼-1.0, where essentially all correspond to clusters located in the bulge (Bica et al 2016).…”
Section: Introductionmentioning
confidence: 99%